KAJIAN FEMINISME DAN NILAI PENDIDIKAN DALAM NOVEL CINTA DI UJUNG SAJADAH KARYA ASMA NADIA - Nurul Kasanah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This study background of the desire of researchers to discover its existence is sometimes seen as a form of resistance. Moreover, by the patriarchal sees women are in position underneath or as a hearty and panoramic views of the sheerThe purpose of this study is to describe and explain: (1) the existence of women contained in the Novel of Love at the End Sajadah KaryaAsma Nadia .; (2) The basic thoughts of feminism; and (3) the value of education in the description of feminism and educational value. Data that has been analyzed by interactive analysis model analysis techniques with three grooves activities (1) data reduction, (2) presentation of data, and (3) conclusion or verification. The results of this study as follows: (1) the existence of women contained in the novel Love at the End of mat work is Asma Nadia; (2) The basic thoughts of feminism, including: independence of women and feminism social character in the novel; and (4) the value of education in the novel Love at the End of mat work is Asma Nadia among others: religious values, moral values, social values, and cultural values.